Muito além do que se vê : representação imagética das xilogravuras de Nena Borges - Chagas, Allini Paulini Nascimento Silva (2024)
This research focuses on the thematic representation of image information, through the analysis of woodcuts by Graciete Correia Borges, artistically known as Nena Borges, the oldest woodcut artist in activity in the State of Pernambuco. To guide this study, the following question stands out as a starting point: how are the themes of Nena Borges' woodcuts represented? This scenario allows us to define the general objective of analyzing the themes portrayed in the woodcuts, experienced in the three levels of image analysis of the iconological method proposed by Erwin Panofsky. More specifically, the objectives aim to: Identify the elements that structurally make up the works under analysis from the pre-iconographic level; describe the symbology of the elements and scenarios identified from the perspective of the iconographic level; contextualize the historical and cultural aspects that characterize the themes of the woodcuts analyzed, supported by the iconological level. Referentially, the theoretical framework is based on the thematic and imagery representation of information. Regarding the methodological path, this study objectively configures itself as a descriptive research of a bibliographic nature , which involves a qualitative approach of an applied nature, from a documentary perspective. As a data collection instrument, documentary analysis was used on the woodcuts produced by the artist, available in online format on the Instagram platform. The results express that the applied methodology enabled a more in-depth and interdisciplinary analysis of the subjects contained in the woodcut works. By describing the elements and interpreting them, based on historical, social and political sources, it was possible to find the respective themes represented by popular culture: dance, games, music, traditions and folkloric figures. Concluding, therefore, that the woodcut is a source of image information relevant to the representative process of cultural manifestations, especially in the Brazilian Northeast, where each carved feature makes up a figure that portrays the memory, customs and identity construction of its people.